Secreted protein kinases regulate cyst burden during chronic toxoplasmosis. (25th August 2016) - Jones, Nathaniel G.; Wang, Qiuling; Sibley, L. David
Abstract: Toxoplasma gondii is an apicomplexan parasite that secretes a large number of protein kinases and pseudokinases from its rhoptry organelles. Although some rhoptry kinases (ROPKs) act as virulence factors, many remain uncharacterized. In this study, predicted ROPKs were assessed for bradyzoite expression then prioritized for a reverse genetic analysis in the type II strain Pru that is amenable to targeted disruption. Using CRISPR/Cas9, we engineered C‐terminally epitope tagged ROP21 and ROP27 and demonstrated their localization to the parasitophorous vacuole and cyst matrix. ROP21 and ROP27 were not secreted from microneme, rhoptry, or dense granule organelles, but rather were located in small vesicles consistent with a constitutive pathway. Using CRISPR/Cas9, the genes for ROP21, ROP27, ROP28, and ROP30 were deleted individually and in combination, and the mutant parasites were assessed for growth and their ability to form tissue cysts in mice. All knockouts lines were normal for in vitro growth and bradyzoite differentiation, but a combined ∆ rop21 /∆ rop17 knockout led to a 50% reduction in cyst burden in vivo . Our findings question the existing annotation of ROPKs based solely on bioinformatic techniques and yet highlight the importance of secreted kinases in determining the severity of chronic toxoplasmosis. Abstract : Toxoplasma gondii contains an expanded family of secreted serine‐threonine protein kinases and pseudokinases that are often duplicated and/or highly polymorphic. The function of most of these proteins is unknown outside of a few that have been studied in the context of acute virulence in the mouse. Here we demonstrate that a subset of these enzymes are upregulated in bradyzoites, secreted into the cyst matrix, and participate development of chronic infections in vivo . Tissue cyst of T. gondii showing the cyst wall stained with lectin (green) and the nuclei of bradyzoites stained with DAPI (blue). Image from N. Jones